Khazana Warna Berdasarkan Hasana Alam dan Budaya Nusantara (1) - Purbasari, Mita; I. K. Jakti, R.A. Diah Resita (Humaniora, 2011)
Using colors for designing purpose is become an important part of designer, such as graphic designer, interior, product, least but not last for architect and artist. Like humans, color need to have a name to identify according to its character, psychology and emotional effect. This research applied the qualitative and quantitative method to give a brief description about color?s name and propose new color naming which based on character, nature, and imagery it evokes. This research will use quantitative and qualitative methods to describe the color names and color names of the new proposed based on the audience choice. Data collected will be used as a proposal of naming colors in Indonesian language that uses the unique natural and cultural riches of Indonesia itself.